2010
DOI: 10.1021/ja100974t
|View full text |Cite
|
Sign up to set email alerts
|

Transition State Analogue Structures of Human Phosphoglycerate Kinase Establish the Importance of Charge Balance in Catalysis

Abstract: Transition state analogue (TSA) complexes formed by phosphoglycerate kinase (PGK) have been used to test the hypothesis that balancing of charge within the transition state dominates enzyme-catalyzed phosphoryl transfer. High-resolution structures of trifluoromagnesate (MgF(3)(-)) and tetrafluoroaluminate (AlF(4)(-)) complexes of PGK have been determined using X-ray crystallography and (19)F-based NMR methods, revealing the nature of the catalytically relevant state of this archetypal metabolic kinase. Importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
94
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 62 publications
(127 reference statements)
8
94
0
Order By: Relevance
“…Studies on hPGK have validated this concept by demonstrating that hPGK prioritizes anionic charge over geometry in selection of MFx for TSA complex formation. [60] Based on the geometry of MFx complexes for a wide range of PTx enzymes, it was demonstrated that charge balance is maintained within a sphere of up to 15 Å around the transferring phosphorus even when that borders on bulk water (Fig. 19B).…”
Section: Charge Balance -Neutralize the "Anionic Shield"mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on hPGK have validated this concept by demonstrating that hPGK prioritizes anionic charge over geometry in selection of MFx for TSA complex formation. [60] Based on the geometry of MFx complexes for a wide range of PTx enzymes, it was demonstrated that charge balance is maintained within a sphere of up to 15 Å around the transferring phosphorus even when that borders on bulk water (Fig. 19B).…”
Section: Charge Balance -Neutralize the "Anionic Shield"mentioning
confidence: 99%
“…19B). [60] A classic example is that of cAPK where charge balance is only achieved by the incursion of the substrate peptide with three +ve charges into a 13.5 Å sphere (Fig. 19A).…”
Section: Charge Balance -Neutralize the "Anionic Shield"mentioning
confidence: 99%
“…A single resonance was observed for the AlF 4 − complex ( δ average =−143.6 ppm, Figure S2) due to fast exchange of the four fluorines between the three binding sites for the oxygens of PO 3 − 1b,1d,1g. Compared with WT, the small upfield chemical shift change (1.6 ppm) and marginal fall in average solvent‐induced isotope shift (SIIS) value (0.2 ppm) for the Arg85′Ala complex indicate that loss of the arginine finger leads to a reduction in the overall tightness of coordination of AlF 4 − (Figure S2).…”
mentioning
confidence: 99%
“…Work to date has focused on probing the reaction mechanism of β-PGM through the introduction of metal fluoride transition-state analogs (TSAs) and computational analysis based on the derived structural data (15)(16)(17)(18)(19)(20)(21). In particular, trifluoromagnesate (MgF 3 − ) has been established as a very close steric and electronic mimic of the planar PO 3 − group (16,20,(22)(23)(24) that represents the energy maximum as phosphorus moves through the plane of the three PO 3 − oxygen atoms (15,21). In addition to providing atomic resolution structures of β-PGM in a near TS conformation, the introduction of metal fluorides allows 19 F NMR to provide measures of the electronic and protonic environment at the catalytic center (20).…”
mentioning
confidence: 99%